Efficacy of cannabidiol (Cannabis sativa L.) in the treatment of Parkinson's disease - Marques, Júlio César Silva; Dantas, Luciana Arantes; Sousa, Tainara Leal de (Brazilian Journal of Science, 2023)
The search for an effective treatment of Parkinson’s disease (PD) is one of the biggest challenges faced by the scientific community, since the already existing treatments cause a lot of long-term side effects. Among the most promising treatments emerging, there is the Cannabidiol (CBD), substance originated from Cannabis sativa, a plant that has been getting a lot of notoriety in the neurological diseases area nowadays. The main purpose of this study is, by a literature review, analyzing the use of CBD in the treatment of symptoms caused by Parkinson in affected patients. In this study writing, extensive research was done based on scientific articles and electronic journals. By analyzing the obtained data, a study about the Cannabidiol’s efficiency in the treatment of Parkinson was obtained. The results imply that the CBD shows an improvement in the patient’s quality of life, promoting neuroprotection and well-being, becoming a promising alternative to PD. Although, a wider range of CBD x placebo studies, a long-term follow-up, measuring the benefits and side effects will be needed.